2022
DOI: 10.3389/fsurg.2022.905394
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Prostatic Artery Embolization in the Treatment of High Risk Benign Prostatic Hyperplasia and its Influence on Postoperative Life Quality of Patients

Abstract: ObjectiveTo evaluate the efficacy, safety and postoperative quality of life of high risk benign prostatic hyperplasia (BPH) patients treated with prostatic artery embolization.Methods34 patients with high-risk BPH were selectedfrom January 2020 to June 2021 in our hospital. All patients were treated with prostatic artery embolization. The changes of international prostate symptom score (IPSS), prostate volume (PV), remaining urine (RU), maximum urine flow rate (Qmax), quality of life scale -74(GQOLI-74), time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…At our center, we performed preoperative PAE on large size BPH patients to reduce volume [ 18 20 ]. Preoperative PAE has several advantages, including less bothersome LUTS, less bleeding, a low incidence of complications during and after surgery, and positive therapeutic effects [ 18 19 20 21 ]. We reviewed the outcomes of preoperative PAE in patients and found that it resulted in reduced hemoglobin loss and reduced surgical time, which ultimately contributed to the rapid recovery of the patient.…”
Section: Preoperative Arterial Embolization For Huge Bphmentioning
confidence: 99%
“…At our center, we performed preoperative PAE on large size BPH patients to reduce volume [ 18 20 ]. Preoperative PAE has several advantages, including less bothersome LUTS, less bleeding, a low incidence of complications during and after surgery, and positive therapeutic effects [ 18 19 20 21 ]. We reviewed the outcomes of preoperative PAE in patients and found that it resulted in reduced hemoglobin loss and reduced surgical time, which ultimately contributed to the rapid recovery of the patient.…”
Section: Preoperative Arterial Embolization For Huge Bphmentioning
confidence: 99%
“…Depression was defined as a critical value of 53, 53 to 62 for mild, 63 to 72 for moderate, and a score higher than 72 for severe depression. For numerical statistics of depression, there were some items that were reverse questions and the scoring criteria should be clearly stated [14].…”
Section: Assessment Of Mental Statusmentioning
confidence: 99%